Disposal of solid urban waste in the municipality of Santa Vitória - MG (Research, Society and Development, 2022)
The Municipality of Santa Vitória, located in the state of Minas Gerais, is one of the Brazilian municipalities that has adhered to the idea of development in recent decades, thanks to the implementation of sugar and ethanol plants and, in parallel with this increase in population, the generation of a greater amount of trash. In this sense, due attention must be given to the destination and disposal of these residues, which will allow a good quality of life and the conservation of the environment. Thus, this study results in a description of the destination of garbage and all urban waste in the municipality of Santa Vitória. Its objective was to know the destination of urban waste in the city of Santa Vitória, through public and legal documents and information on waste management in the municipality, visit and observation in addition to bibliographic research in scientific literature in order to contribute to the reflection on the impact of the generation of waste discarded daily in the environment, as well as discussing ways to face this issue. An analysis of documents, legislation and literature on the subject was carried out, and observation and photographic record of the activities and places involving the destination of urban waste in the municipality. Through the research carried out, it is clear that there are still many improvements to be made, since there is no selective collection implemented, which would promote the generation of employment and income. It is important to adopt these measures as a way to reduce the volume of material that goes to the local landfill, increase its useful life and reduce the demand for natural resources. It is worth mentioning the importance of the measures already taken, such as turning the controlled landfill into a sanitary landfill, as it is a method of final disposal with greater advantages, considering the reduction of negative environmental impacts and risks to the health of the population.